Case report: Pelvic abscess after cesarean section and hysterectomy: Predstavitev primera: Pelvični absces kot zaplet carskega reza in histerektomije - Krajnc, Klavdija; Takač, Iztok; Mujezinović, Faris; Horvat, Matjaž; Kuder, Lucija (Acta Medico-Biotechnica, 2021)
Purpose: The purpose of this article was to present the case of a pelvic abscess, which developed after an emergency cesarean section followed by a hysterectomy, to identify the risk factors, and describe a minimally invasive technique for abscess drainage.Case report: We present a 30-year-old patient at 35 + 4 weeks gestation who had an emergency cesarean section. The indication for the cesarean section were four previous cesarean sections. She had severe postpartum bleeding due to uterine atony and disseminated intravascular coagulopathy, which did not resolve with conservative treatment. A few days later, a pelvic abscess formed and complicated the post-operative recovery.Conclusion: A pelvic abscess is a rare complication following obstetrics surgery; however, it is important to take
Keywords: pelvic abscess; hysterectomy complication; cesarean section; postpartum bleeding